2013
DOI: 10.12927/whp..17597
|View full text |Cite
|
Sign up to set email alerts
|

Drug Regulation and Control in Nigeria: the Challenge of Counterfeit Drugs

Abstract: The primary objective of this study is to establish the factors that have contributed to the preponderance of counterfeit drugs in Nigeria despite the laws. Data was gathered by a combination of the use of questionnaires and oral interviews. The results suggest that drug laws were adequate falling short only in their implementation. The task forces were rated as ineffective arising from corruption, communication gaps, lack of adequate funds, lack of vehicles, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 9 publications
4
83
0
Order By: Relevance
“…Previous studies showed that university undergraduate students are involved in misuse and abuse of various drugs 7,12,13,14 . However, in Nigeria, implementation of regulations governing the distribution, sales and use of antibiotics and other prescription medicines are weak, and sometimes non-existent 15 . As a result, the populace are at more risk of irrational use of drugs including antibiotics 2,7,12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that university undergraduate students are involved in misuse and abuse of various drugs 7,12,13,14 . However, in Nigeria, implementation of regulations governing the distribution, sales and use of antibiotics and other prescription medicines are weak, and sometimes non-existent 15 . As a result, the populace are at more risk of irrational use of drugs including antibiotics 2,7,12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…As explained above during the procedures carried out as part of parallel trade, changes in packaging, relabelling and reconditioning provide opportunities for falsifying and counterfeiting even legitimate products [45,[62][63][64][65][80][81][82].…”
Section: International Trade -On the Brink Of Changementioning
confidence: 99%
“…Companies are required to submit applications for the registration of medicines for the evaluation and approval; (3) Undertake appropriate investigations into the production premises and raw materials for drugs and establish relevant quality assurance systems including certification of the production sites and regulated products; (4) Undertake inspection of drugs' whole and retail sellers owned by both public or private sectors; (5) Compile standard specifications and regulations and guidelines for the production, importation, exportation, sale and distribution of drugs, cosmetics, etc. (6) Control of quality of medicines: This will be done by regular inspection and post-marketing surveillance; (7) Licensing of pharmacy premises (i.e., pharmaceutical plants, wholesalers and retail pharmacies); (8) Maintain national drug analysis laboratories for the pre-and post-marketing analysis of medicines; (9) Coordination with states departments of pharmacy to ensure the enforcement of the Act and its rules and directives.…”
Section: Aim and Objectivementioning
confidence: 99%